A case of McKusick-Kaufman syndrome - Son, Se-Hyung (The Korean Pediatric Society, 2011)
McKusick-Kaufman syndrome (MKS) is an autosomal recessive multiple malformation syndrome characterized by hydrometrocolpos (HMC) and postaxial polydactyly (PAP). We report a case of a female child with MKS who was transferred to the neonatal intensive care unit of Seoul National University Children's Hospital on her 15th day of life for further evaluation and management of an abdominal cystic mass. She underwent abdominal sonography, magnetic resonance imaging, genitography and cystoscopy which confirmed HMC with a transverse vaginal septum. X-rays of the hand and foot showed bony fusion of the left third and fourth metacarpal bones, right fourth dysplastic metacarpal bone and phalanx, right PAP and hypoplastic left foot with left fourth and fifth dysplastic metatarsal bones. In addition, she had soft palate cleft, mild hydronephroses of both kidneys, hypoplastic right kidney with ectopic location and mild rotation, uterine didelphys with transverse vaginal septum and low-type imperforated anus. She was temporarily treated with ultrasound-guided transurethral aspiration of the HMC. Our patient with HMC and PAP was diagnosed with MKS because she has two typical abnormality of MKS and she has no definite complications of retinal disease, learning disability, obesity and renal failure that develop in Bardet-Biedl syndrome, but not in MKS until 33 months of age. Here, we describe a case of a Korean patient with MKS.